Parkinson’s disease in women - Fiszer, Urszula (Przewodnik Lekarza/Guide for GPs, 2008)
Little is known regarding the effect that gender has on the development and course of Parkinson’s disease (PD). The incidence of PD is greater in men than in women. Recent attention has been focused on the relationship between sex hormone levels and the development of PD. It is known that oestrogen has effects on dopamine transmission, therefore researchers are interested in its possible use to either slow the progression or reduce the risk of PD. The article below presents data indicating that the nature of PD and its response to therapy are related to gender.